Pengaruh Kualitas Produk Dan Promosi Terhadap Volume Penjualan Bubuk Teh Gambir Bersama Di Pakpak Bharat - Bancin, Sampeida; Sihombing, Natalia E.; Pasaribu, Vera A.R. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This study aims to determine the effect of product quality on sales volume and to determine the effect of promotion on sales volume of Gambir Tea Powder consumers in Salak District. The type of research used in this study is a quantitative approach. The population in this study were all Gambir Tea Powder Consumers. Based on the Slovin formula, the sample used in this study was 100 respondents who were taken randomly representing each village. The results of the study showed that product quality significantly affects purchasing decisions, this is shown in the results of the partial test (t-test) The calculated t value (X1) 16.350 > t table 1.984 significance value 0.000 < 0.05 and the results of the partial test (t-test) The calculated t value (X2) 17.525 > t table 1.984 significance value 0.000 < 0.05. The coefficient of determination (R2) was obtained at 0.784, meaning that the Purchasing Decision variable can be explained by the product quality and promotion variables by 78.4% and the remaining 21.6% is influenced by other variables outside the variables of this study. The conclusion in this study is that product quality and promotion have a positive and significant effect on sales volume for consumers of Gambir Tea Powder in Salak District, Pakpak Bharat Regency.